Sosialisasi Perencanaan Keuangan Dalam Meningkatkan Pendapatan Bagi UMKM di Desa Sei Buluh Kecamatan Perbaungan - Murni Dahlena Nasution; Sari Wulandari (Forum Kerjasama Pendidikan Tinggi, 2021)
The new normal era is a time when all people are required to keep their distance by doing social distancing. The main cause is the corona virus or the covid-19 virus which has had a devastating impact on economies around the world. So in this case all levels of society are also required to live clean and healthy lives in order to stop the spread of the virus. Through the KKN (independent) Program - Learning to care about Covid 19, the government collaborates with the Muslim Nusantara Al Washliyah University in its implementation through students who go directly to Sei Buluh Village, Perbaungan District, Serdang Bedagai Regency. KKN activities are carried out for 5 weeks with a program of activities including counseling and mentoring for the community and MSME players in financial planning to increase income and conducting education on making disinfectants so that all forms of germs and viruses are lost from the environment and socialization of wearing masks outside the home. The result of this activity was the enthusiasm of the villagers